The Influence of Mufradat Memorization Method on Improving Students' Arabic Text Translating Ability - Arif Widodo; M Syafiq Irwansyah Syafiq (Kilmatuna: Journal Of Arabic Education, 2023)
Method of Memorizing Mufradat, Memorizing Text, Arabic AbstractAbstract The Arabic language learning process at the Tarbiyatus Shibyan Kemantren Vocational School is not running effectively. Students face a problem mastering mufrodat, even though vocabulary is one of the language elements that must be mastered to be proficient in communicating. This is due to the application of less varied learning methods at Tarbiyatus Shibyan Kemantren Vocational School. Seeing these problems, this research was carried out. The problem formulation for this research consists of: 1) How does the Mufradat Memorization Method apply to improving the ability to translate Arabic texts for class X students at Tarbiyatus Shibyan Vocational School, Kemantren? Kemantren? This type of research includes quantitative experimental research with a One Group pretest posttest design model, the research instruments used are: Observation, Documentation, Interviews and Tests. The results of this research are: 1) The Mufradat Memorization Method is suitable and appropriate to be applied to class X students at Tarbiyatus Shibyan Kemantren Vocational School. By using the Mufradat Memorization Method in learning Arabic, students will quickly understand the lessons being taught. 2) Applying the Mufradat Memorization Method in learning can improve the ability to translate Arabic texts in class There is a significant and appropriate influence to improve students' ability to translate Arabic texts, this is proven by the T-test analysis results which are higher than at the 0.05 significance level in the T distribution table, namely 11.608 > 1.671. This means that the Mufradat memorization method has a significantly strong influence. From the results of this research, it is recommended that the Tarbiyatus Shibyan Kemantren Vocational School can use varied methods in learning Arabic, including the use of the mufradat memorization method to improve the ability to translate Arabic texts, so that students will quickly understand the material presented by the teacher